Wireless optogenetic stimulation on the prelimbic to the nucleus accumbens core circuit attenuates cocaine-induced behavioral sensitization - Min Jeong Ku; Choong Yeon Kim; Jong Woo Park; Seohyeon Lee; Eun Young Jeong; Jae-Woong Jeong; Wha Young Kim; Jeong-Hoon Kim (Neurobiology of Disease, 2024)
Behavioral sensitization is defined as the heightened and persistent behavioral response to repeated drug exposure as a manifestation of drug craving. Psychomotor stimulants such as cocaine can induce strong behavioral sensitization. In this study, we explored the effects of optogenetic stimulation of the prelimbic (PL) to the nucleus accumbnes (NAc) core on the expression of cocaine-induced behavioral sensitization. Using wireless optogenetics, we selectively stimulated the PL-NAc core circuit, and assessed the effects of this treatment on cocaine-induced locomotor activity and accompanying changes in neuronal activation and dendritic spine density. Our findings revealed that optogenetic stimulation of the PL-NAc core circuit effectively suppressed the cocaine-induced locomotor sensitization, accompanied by a reduction in c-Fos expression within the NAc core. Moreover, optogenetic stimulation led to reduction in dendritic spine density, particularly thin and mushroom spine densities, in the NAc core. This study demonstrates that cocaine-induced locomotor sensitization can be regulated by optogenetic stimulation of the PL-NAc core circuit, providing insights into the crucial role of this circuit in psychomotor stimulant addiction.